Gambaran Kejadian Stunting Pada Balita Di Puskesmas Antang Kota Makassar (Window of Public Health Journal, 2025)
Stunting is a chronic nutritional problem caused by prolonged inadequate nutritional intake, generally due to food intake that does not meet nutritional needs. The government is working to address the problem of malnutrition and stunting. Improving nutrition and reducing the prevalence of stunting in children under two years old (baduta) from 32.9% in 2018 to 28% in 2019 is one of the national development priorities, as stated in the 2015-2019 national medium-term development plan. This study uses a descriptive analysis method with a quantitative approach. The results of this study show that of the 35 toddler respondents at the Antang Health Center in 2022, based on low birth weight in the Antang Health Center work area of ​​35 respondents, 14 toddlers had a birth weight of ≥2500 grams and 21 toddlers had a birth weight of